2014
DOI: 10.1186/1742-2094-11-3
|View full text |Cite
|
Sign up to set email alerts
|

Translocator protein (18 kDa) (TSPO) is expressed in reactive retinal microglia and modulates microglial inflammation and phagocytosis

Abstract: BackgroundThe translocator protein (18 kDa) (TSPO) is a mitochondrial protein expressed on reactive glial cells and a biomarker for gliosis in the brain. TSPO ligands have been shown to reduce neuroinflammation in several mouse models of neurodegeneration. Here, we analyzed TSPO expression in mouse and human retinal microglia and studied the effects of the TSPO ligand XBD173 on microglial functions.MethodsTSPO protein analyses were performed in retinoschisin-deficient mouse retinas and human retinas. Lipopolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

20
150
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(174 citation statements)
references
References 41 publications
20
150
2
2
Order By: Relevance
“…Increased TSPO mRNA and protein levels have been reported in activated BV2 microglia induced by LPS, a pro-inflammatory inducer, whereas multiple pro-inflammatory marker genes, including interleukin-6 (IL-6) and inducible nitric oxide synthase, were suppressed by the TSPO ligand XBD173, implicating a possible correlation of TSPO and proinflammatory microglia (Karlstetter et al, 2014). Moreover, a PET imaging study in nonhuman primates given low-dose intravenous LPS showed increased whole-brain uptake of 11 C-PBR28 in parallel with elevated serum levels of IL-1␤ and IL-6, indicating that TSPO may be associated with pro-inflammatory microglial activation (Hannestad et al, 2012).…”
mentioning
confidence: 99%
“…Increased TSPO mRNA and protein levels have been reported in activated BV2 microglia induced by LPS, a pro-inflammatory inducer, whereas multiple pro-inflammatory marker genes, including interleukin-6 (IL-6) and inducible nitric oxide synthase, were suppressed by the TSPO ligand XBD173, implicating a possible correlation of TSPO and proinflammatory microglia (Karlstetter et al, 2014). Moreover, a PET imaging study in nonhuman primates given low-dose intravenous LPS showed increased whole-brain uptake of 11 C-PBR28 in parallel with elevated serum levels of IL-1␤ and IL-6, indicating that TSPO may be associated with pro-inflammatory microglial activation (Hannestad et al, 2012).…”
mentioning
confidence: 99%
“…This broad spectrum of bioactivities makes it an attractive theurapeutic drug target and a number of TSPO ligands has been synthesised and evaluated for their functional effects on TSPO and development of potential therapeutic agents (Szewczyk and Wojtczak, 2002;Galiegue et al, 2003;Karlstetter et al, 2014;Selvaraj et al, 2015). In addition, the development of radiolabelled TSPO ligands as molecular markers for imaging (Katsifis et al, 2000;Fookes et al, 2008;Pulli and Chen, 2014;Katsifis et al, 2004) helped localizing and monitoring the TSPO upregulation on activated microglia and/or astrocytes which is one of the hallmarks of neuroinflammation and neurodegeneration (Wilms et al, 2003;Girard et al, 2008;Mattner et al, 2011;Daugherty et al, 2013;Mattner et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is hypothesized that the Alanine to Threonine substitution at position 147 results in a conformational change in TSPO structure that influences its interaction with ligands. 36,38,39 Differences in binding affinity may have important implications for the etiopathology of AD; TSPO ligands have been shown to ameliorate neuroinflammation in vitro, 40 reverse neuropathology and behavioral decline in AD mouse models, 41 reduce Ab 42 -induced neurodegeneration in drosophila, 42 as well as confer neuroprotective and regenerative effects in vivo and in vitro. [43][44][45][46] Despite this potential involvement of TSPO in the etiopathology of neurodegenerative disorders, and the well-known links between inflammation, cerebrovascular disease, and AD, no studies to date have investigated the effect of rs6971 on MRI-based phenotypes or inflammatory biomarkers.…”
Section: Introductionmentioning
confidence: 99%